What Basophil Testing Tells Us About CSU Patients – Results of the CORSA Study - Marcelino, João; Baumann, Katrine; Skov, Per Stahl; Pereira Santos, Maria Conceição; Wyroslak, Inga; Scheffel, Jörg; Altrichter, Sabine; Woetmann, Anders; Pereira-Barbosa, Manuel; Costa, Célia; Maurer, Marcus (Frontiers in Immunology, 2021)
Basophil testing is the most effective single approach for diagnosing type-IIb autoimmune chronic spontaneous urticaria (TIIbaiCSU). A positive basophil test has been linked to long disease duration, higher disease activity, a poor response to antihistamines and omalizumab, and a better response to cyclosporine and fenebrutinib. As of now it is unclear what other features are connected to a positive basophil test in chronic spontaneous urticaria (CSU). We aimed to identify features of basophil test-positive CSU patients. We performed a cross-sectional study of 85 CSU patients. Basophil testing was done with the basophil activation test (BAT) and the basophil histamine release assay (BHRA). Data were analysed using SPSS: Student’s t-test, Chi-square test, Odds Ratio, Spearman’s correlation test. Of 85 CSU patients, 44% and 28% tested positive with the BAT and BHRA, respectively. These patients showed higher disease activity and impact, lower levels of disease control and total serum IgE, as well as higher rates of having a positive autologous serum skin test (ASST), angioedema, nocturnal symptoms, symptoms for >5 days/week, and thyroid autoantibodies. The ASST, by itself, was not a good predictor of basophil test results, but it predicted a positive basophil test in up to 100% of cases when combined with angioedema, thyroid autoantibodies or low IgE. In conclusion, a positive basophil test is linked to known features of TIIbaiCSU and novel characteristics including nocturnal symptoms. Further studies on basophil test-positive and -negative CSU patients can help to better understand CSU endotypes and to develop better management approaches.